Long-term efficacy and effectiveness of a behavioural and community-based exercise intervention (Urban Training) to increase physical activity in patients with COPD: a randomised controlled trial. Issue 4 (18th October 2018) - Arbillaga-Etxarri, Ane; Gimeno-Santos, Elena; Barberan-Garcia, Anael; Balcells, Eva; Benet, Marta; Borrell, Eulàlia; Celorrio, Nuria; Delgado, Anna; Jané, Carme; Marin, Alicia; Martín-Cantera, Carlos; Monteagudo, Mónica; et al.
There is a need to increase and maintain physical activity in patients with chronic obstructive pulmonary disease (COPD). We assessed 12-month efficacy and effectiveness of the Urban Training intervention on physical activity in COPD patients. This randomised controlled trial (NCT01897298) allocated 407 COPD patients from primary and hospital settings 1:1 to usual care (n=205) or Urban Training (n=202). Urban Training consisted of a baseline motivational interview, advice to walk on urban trails designed for COPD patients in outdoor public spaces and other optional components for feedback, motivation, information and support (pedometer, calendar, physical activity brochure, website, phone text messages, walking groups and a phone number). The primary outcome was 12-month change in steps·day −1 measured by accelerometer. Efficacy analysis (with per-protocol analysis set, n=233 classified as adherent to the assigned intervention) showed adjusted (95% CI) 12-month difference +957 (184–1731) steps·day −1 between Urban Training and usual care. Effectiveness analysis (with intention-to-treat analysis set, n=280 patients completing the study at 12 months including unwilling and self-reported non-adherent patients) showed no differences between groups. Leg muscle pain during walks was more frequently reported in Urban Training than usual care, without differences in any of the other adverse events. Urban Training, combining behavioural strategies with unsupervised outdoor walking, was efficacious in increasing physical activity after 12 months in COPD patients, with few safety concerns. However, it was ineffective in the full population including unwilling and self-reported non-adherent patients. Urban Training in COPD increased physical activity after 12 months but not in self-reported non-adherent patients http://ow.ly/dc2C30lnAEs